2024
DOI: 10.1128/mbio.02407-23
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Omicron infection augments the magnitude and durability of systemic and mucosal immunity in triple-dose CoronaVac recipients

Yuxin Chen,
Tiantian Zhao,
Lin Chen
et al.

Abstract: The inactivated whole-virion vaccine, CoronaVac, is one of the most widely used coronavirus disease 2019 (COVID-19) vaccines worldwide. There is a paucity of data indicating the durability of the immune response and the impact of immune imprinting induced by CoronaVac upon Omicron infection. In this prospective cohort study, 41 recipients of triple-dose CoronaVac and 14 unvaccinated individuals were recruited. We comprehensively profiled adaptive immune parameters in both groups, including spike-specific immun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Noteworthy, in the present study, SARS-CoV-2 anti-S IgA antibodies, a surrogate marker for local immunity, were still present in most PLWH at 8 -9 months after infection or vaccination; similar to the data reported in longitudinal follow-up studies in the general population, showing persistent adaptative systemic and local immune responses up to two years, with more durable and organized immune responses after recovery from COVID-19 [37]. Recent studies have also demonstrated that breakthrough infections with the currently circulating Omicron variants enhance both the breadth and persistence of all types of specific immune responses, including nasal spike-specific IgA levels [42]. Longitudinal studies have also demonstrated a rapid activation of SARS-CoV-2 specific cellular immune responses during breakthrough infections, explained both by the recall of CD4+ and CD8+ spike-specific memory cells, and de novo T cell responses [43].…”
Section: Discussionsupporting
confidence: 79%
“…Noteworthy, in the present study, SARS-CoV-2 anti-S IgA antibodies, a surrogate marker for local immunity, were still present in most PLWH at 8 -9 months after infection or vaccination; similar to the data reported in longitudinal follow-up studies in the general population, showing persistent adaptative systemic and local immune responses up to two years, with more durable and organized immune responses after recovery from COVID-19 [37]. Recent studies have also demonstrated that breakthrough infections with the currently circulating Omicron variants enhance both the breadth and persistence of all types of specific immune responses, including nasal spike-specific IgA levels [42]. Longitudinal studies have also demonstrated a rapid activation of SARS-CoV-2 specific cellular immune responses during breakthrough infections, explained both by the recall of CD4+ and CD8+ spike-specific memory cells, and de novo T cell responses [43].…”
Section: Discussionsupporting
confidence: 79%
“…Noteworthy, in the present study, SARS-CoV-2 anti-S IgA antibodies, a surrogate marker for local immunity, were still present in most PLWH at 8–9 months after infection or vaccination, similar to the data reported in longitudinal follow-up studies in the general population, showing persistent adaptative systemic and local immune responses up to two years, with more durable and organized immune responses after recovery from COVID-19 [ 38 ]. Recent studies have also demonstrated that breakthrough infections with the currently circulating Omicron variants enhance both the breadth and persistence of all types of specific immune responses, including nasal spike-specific IgA levels [ 43 ]. Longitudinal studies have also demonstrated a rapid activation of SARS-CoV-2-specific cellular immune responses during breakthrough infections, explained both by the recall of CD4+ and CD8+ spike-specific memory cells and de novo T cell responses [ 44 ].…”
Section: Discussionmentioning
confidence: 99%